Komunikasi Pengajaran Yesus Menjadi Role Model Bagi Pendidik Kristen - Yosia Belo; Rika S. (STT Pelita Dunia, 2022)
Abstract: This paper examines Jesus' teaching communication as a role model for Christian educators. The research topic is inseparable from the current situation, where most teachers no longer pay attention to communication when teaching, so it impacts the ineffectiveness of teaching and learning activities. Several conclusions can be obtained using qualitative research or, more precisely, a literature review. The findings are (1) Jesus communicated His teaching in the form of parables; (2) Jesus communicated His teachings with practical examples; (3) Jesus communicated His teaching while preaching; (4) Jesus communicated His teaching with creative actions; and (5) Jesus communicated His teachings with full authority and role model. If Christian educators want to be role models, then every Christian educator must communicate each of the teachings with simple analogies, actual and known by every student, or using parables in the context of Jesus' teaching. Then today's Christian educators must also communicate their teaching with practical examples in sermon language or language that is practical and easy for every student to digest. Not only that, but every Christian educator must also take creative actions to convey and communicate each of their teachings. Abstrak: Tulisan ini meneliti tentang Komunikasi Pengajaran Yesus menjadi role model bagi pendidik Kristen. Topik ini diteliti tidak terlepas dengan kondisi masa kini, di mana kebanyakan guru tidak lagi memperhatikan komunikasi ketika mengajar sehingga berdampak kepada kurang efektifnya kegiatan belajar-mengajar yang dilakukan. Dengan menggunakan penelitian kualitatif atau lebih tepatnya kajian literatur, maka dapat diperoleh beberapa kesimpulan yaitu (1) Yesus mengkomunikasikan pengajaran-Nya dalam bentuk perumpamaan; (2) Yesus mengkomunikasikan pengajaran-Nya dengan contoh-contoh praktis; (3) Yesus mengkomunikasikan pengajaran-Nya sambil berkhotbah; (4) Yesus mengkomunikasikan pengajaran-Nya dengan tindakan-tindakan yang kreatif; dan (5) Yesus mengkomunikasikan pengajaran-Nya dengan penuh otoritas dan keteladanan. Apabila pendidik Kristen hendak menjadikannya sebagai role model maka setiap pendidik Kristen harus mengkomunikasikan setiap pengajarannya dengan analogi-analogi yang sederhana, real dan diketahui oleh setiap peserta didik atau kalau dalam konteks Yesus mengajar, menggunakan perumpamaan. Pendidik Kristen masa kini juga harus mengkomunikasikan pengajarannya dengan contoh-contoh yang praktis dengan bahasa khotbah atau bahasa yang praktis dan mudah dicerna oleh setiap peserta didik. Tidak hanya itu, setiap pendidik Kristen juga perlu melakukan tindakan-tindakan kreatif untuk menyampaikan dan mengkomunikasikan setiap pengajarannya.